Preventing Biofilm Formation by Dairy-Associated Bacteria Using Peptide-Coated Surfaces - Friedlander, Alon; Nir, Sivan; Reches, Meital; Shemesh, Moshe (Frontiers in Microbiology, 2019)
Biofilm-forming bacteria, which colonize the surfaces of equipment in the dairy industry, may adversely affect the safety and quality of the milk and its products. Despite numerous efforts to combat biofilm formation, there is still no effective technological means to thoroughly solve the biofilm problem in the dairy industry. Here, we introduced peptide-based coating in order to modify the physical properties of the stainless steel surface by affecting its availability for bacterial adhesion. We found that the coated surface displays a notable decrease in the ability of bacterial cells to attach and to subsequently form biofilm by Gram-positive Bacillus licheniformis and Gram-negative Pseudomonas aeruginosa. Furthermore, the coated surface retained its anti-biofilm ability following its exposure to raw milk. Importantly, the modified surface did not affect the milk coagulation process or its nutritious properties and quality. Overall, this anti-biofilm approach may serve as an attractive solution for the dairy industry in its struggle against bacterial contamination.